Best Approximations of q-Ellipsoids in Spaces S_ϕ^p,μ - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We find exact values of the best approximations and basic widths of q-ellipsoids in the spaces S_ϕ^p,μ for q > p > 0.